Awareness and Treatment Seeking Behaviour of People Affected With Malaria in Coastal South India - B Unnikrishnan; Anan Jaiswal; B Reshmi (Tehran University of Medical Sciences, 2008)
Background: Malaria is a serious global health challenge. Mangalore, Karnataka, India is an endemic area for malaria and there has not been much research on this area. Thus it has been felt that this study will provide an insight into efficacy of the current malaria control programs and identifying targets for future educational campaigns and provide guidance for existing programs.Methods: The study was community based descriptive study and the data were collected by interviewing the subjects who had malaria infections in the last 12 months. The study duration was 24 months.Results: Two hundred and five individuals >= 15 years of age and who had at least 1 episode of malaria in the past 12 months were interviewed. Within the study population, 80.5% of the subjects correctly identified mosquitoes as the source of malaria. Seventy one percent of the interviewed subject completed the full course of medicine prescribed to them. Eighty one percent of the respondent said that no health education was given to them regarding prevention of malaria majority of the respondents spent between $10 to $30 for treatment of malaria.Conclusions: The malaria awareness campaign should be intensified as not all the people are aware to   the cause of malaria and compliance to the treatment has to be increased by sensitizing the patients.